Dromologi dan Era Flash Sale: Tinjauan Geliat Manusia dalam Cyberspace - Bagus Ardiyansyah; Drajat Tri Kartono; Argyo Demartoto (SIMULACRA: JURNAL SOSIOLOGI, 2019)
The rate of development of information and communication technology today is increasingly massive and almost every time gives birth to new. Consumer activity has also shifted to the digital sector, or more massive in the artificial sector than in the real world. This is an era that is influenced by digital-economy, namely posteconomy. With its advantages, space-time freezing and freezing occur or in short space-time efficiency. The output of a human being created as a thinker, which uses his passion through the use of digital literacy in economic lines. One marketplace for buying daily necessities that are often visited by real people is Shopee. For the sake of maintaining the existence in the minds of consumers, Shopee began to aggressively take actions to link consumers or the community, one of them by making a flash sale. Furthermore, through descriptive-explanative qualitative methods with the type of library research; praxis loading and freezing of space-time (dromology) that happened as described by Paul Virilio in digital development, as a responsive substitution of real economic activity into the digital economy. Shopee uses strategic reality, the power of knowledge and the power of movement, even to make the body a commodity repertoire.